Manajemen budaya organisasi - Tasya Aspiranti (Universitas Islam Bandung, 2010)
Organizational culture as the set of shared values and norms that control orga nizational members' interactions with each other and with people outside organization. An organization's culture can be used to increase orga nizational effectiveness. This is because organizational culture controls the way members make decisions, the way interpret and manage the organizatio n's environment. In adaptif organi zation, organizational culture change absolutely must be taken to raise effective culture that can support organizational goals. This paper explains the importance of people in organization as organizational culture shaper, any kind theory of organizational culture, organizational culture management and how to manage culture in organization. Some real organizational culture cases are presented in this paper and organizational culture management paradigm as conclusion is presented in the end of paper.Key words : organizational culture management